Relationship between Internet addictions and academic performance among Afghan universities students - Ghulami, Hassan Rahnaward; Ab Hamid, Mohd Rashid; Ibrahim, Mohd Reza; Hikmat, Ali; Aziz, Hussein (International Journal of Innovative Research and Scientific Studies, 2018)
This study evaluates the relationship between Internet addiction and academic performance among students of eight Afghan universities. The differences between internet addiction in terms of gender was also identified. The survey/research method adopted the Internet Addiction Test (IAT) based on Young’s survey applied with some modifications. From 1000 distributed questionnaires only 976 participants (358 females, and 618 males) were responded completely. The descriptive analysis was used to identify the demographic characteristics of student’s Internet usage profile. The independents sample t-test was performed to determine the differences in the level of Internet addiction in terms of gender. Statistical significance was set at a value of p <0.01. Likewise, the correlation test was implemented to identify the relationship between Internet addiction and academic performance, with referencing of sample. The results indicated that statistically there is a significant correlation among Internet addiction and academic performance. Results also indicated that statistically there were significant differences between Internet addictions in terms of demographic characteristics. This study suggests that future researchers need to work on large sample while conducting the related research. It emphasizes that students should concentrate more on their academic activities than spending time on unnecessary Internet surfing. Findings also revealed that, in Afghanistan the problem of Internet addiction is not a serious challenge, but this information should be disseminated among undergraduate university students to stop the indulgent in using the Internet.